Effect of sodium hydroxide concentration on strength and microstructure of alkali-activated natural pozzolan and limestone powder mortar - Adewumi, Adeshina Adewale (Elsevier Ltd, 2021)
The present study evaluates the effect of sodium hydroxide concentrations on strength, bond properties, reaction products and the microstructures of binary blended alkali-activated volcanic natural pozzolan and limestone powder (AANL) mortar. Six AANL mortar were prepared with alkaline activators of 4–14 M NaOH(aq) and Na2SiO3(aq) such that the activators ratio was 1:1. Curing was done at 75 °C for 24 h duration. The maximum 90-day compressive strength of 31.3 MPa was achieved with 10 M NaOH(aq) while 76% of the strength could be achieved within three days when 10 M NaOH was used. The 28-day tensile strength of 2.32 MPa was achieved with 14 M NaOH(aq). XRD characterizations revealed that activation with a strong concentration of sodium hydroxide (10 M NaOH(aq)) led to the formation of anorthite (CaAl2Si2O8) and gehlenite (Ca0.Al2O3SiO2). SEM + EDX indicated that strong alkali (10 M NaOH) enhanced microstructural density compared to that of mild alkali (4 M NaOH(aq)).